Integrasi Pendidikan Karakter dalam Pembelajaran Pendidikan Agam Islam Di Sekolah Dasar Negeri 21 Lembah Melintang - Laila Sapitri (Jurnal Pendidikan dan Humaniora Rumbio, 2025)
This study aims to describe the process of integrating character education into Islamic Religious Education (PAI) learning in elementary schools 21 Lembah Melintang. Character education is a crucial aspect in shaping students' personality and noble character from an early age. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation involving several PAI teachers in elementary schools 21 Lembah Melintang. The findings show that character values such as religiousness, honesty, discipline, responsibility, and tolerance are integrated into PAI learning through active learning methods, teacher role modeling, and religious activities at school. However, the implementation of this integration still faces challenges, such as the lack of teacher training and limited instructional time. Therefore, support from all parties schools, families, and communities is needed to ensure that the integration of character education into PAI learning runs effectively and sustainably.